Association of GPS-Based Logging and Manual Confirmation of the First Responders' Arrival Time in a Smartphone Alerting System: An Observational Study. (2nd November 2022) - Ganter, Julian; Pooth, Jan-Steffen; Damjanovic, Domagoj; Trummer, Georg; Busch, Hans-Jörg; Baldas, Klemens; Schmitz, Daniel; Müller, Michael P.
Abstract: The latest guidelines for cardiopulmonary resuscitation recommend that in case of suspected cardiac arrest first responders, who are close to the emergency location, should be notified by a smartphone app or text message. Smartphone Alerting Systems (SAS) aim to reduce the resuscitation-free interval. Thus, there is a need for uniform reporting of process times. Objective: To compare the response times in a SAS either by using global positioning system (GPS) data or by manual confirmation of first responders arriving at the scene. Methods : In the region of Freiburg (Southern Germany, 1, 531 km 2, 493, 000 inhabitants), a SAS is activated when the emergency dispatch center receives a call regarding suspected cardiac arrest. First responders who accept a mission are tracked using GPS. GPS-based times are logged for each responder when their position is within a radius of 100, 50, or 10 meters around the geographical position of the reported emergency. When arriving at the patient location, the first responders manually confirm "arrived" via their app. GPS-based and manually confirmed response arrival times were compared for all cases between 1 October and 31 March. Results: 192 missions with correct manual logging of the arrival time were included. GPS-based times were available in 175 (91%), 100 (52%), and 30 (16%) cases within radii of 100, 50, and 10 meters, respectively. GPS arrival times were approximately 1.5 minutes shorter when using a 100-meter radius and significantly longer when using a 10-meter radius. No difference was found for a 50-meter radius, but this would result in a lack of data in nearly half of the cases. Conclusion: GPS-based logging of arrival times leads to missing data. A 100-meter circle is associated with a low number of missing values, but 1.5 minutes must be added for the last 100 meters the first responder has to move. A wide range of the difference in response times (GPS vs. manual confirmation) must be regarded as a disadvantage. Manual confirmation reveals precise response times, but first responders may forget to confirm when they arrive. Trial registration : DRKS00016625 (14 April 2019).